Phosphate Limitation Increases Content of Protease Inhibitors in the Cyanobacterium Microcystis aeruginosa - Burberg, Christian (Toxins (Basel), 2020)
Increased anthropogenic nutrient input has led to eutrophication of lakes and ponds, resulting worldwide in more frequent and severe cyanobacterial blooms. In particular, enhanced availability of phosphorus (P) can promote cyanobacterial mass developments and may affect the content of secondary metabolites in cyanobacteria, such as protease inhibitors (PIs). PIs are common among cyanobacteria and have been shown to negatively affect herbivorous zooplankton. Here, we test the hypothesis that P-limitation reduces the growth of Microcystis, but increases the content of PIs. In batch culture experiments with eight different initial phosphate concentrations (5–75 µM) we determined growth, stoichiometry, and PI content of Microcystis aeruginosa NIVA Cya 43. This strain produces the protease inhibitor BN920 that is converted by chlorination to CP954, which constitutes the major PI in this strain. C:N:P-ratios of the biomass indicated variation of P-limitation with treatment and time. When normalized to biomass, the PI content varied up to nearly nineteen-fold with treatment and time and was highest in the low-P treatments, especially during the mid-exponential growth phase. However, these effects were alleviated under nitrogen co-limitation. The content of CP954 showed an inverse u-shaped response to growth rate and C:N-ratio of the cyanobacterial biomass, whereas it increased with cyanobacterial C:P. The results indicate that P-limitation supports a higher content of defensive PIs and may indirectly foster cyanobacterial blooms by increasing the negative interference of cyanobacteria with their consumers.